(untitled) (Contemporary Journal of Social Science Review, 2025)
This study looks into the connection of rhetorical leadership and employees’ job performances, with the main focus on the mediating role of employee commitment. Rhetorical leadership is a kind of leading that is so well defined by the communicative style (and the persuasive power that it has with its audience) that it not recognizes only rhetorical skills as part of leadership, but also the more important capacity of leaders to inspire and to motivate their team members by using words. This is the kind of leadership that enhances job performance by cultivating a stronger sense of commitment among employees. To investigate this connection, the research carries out a comprehensive review of the current literature along with empirical scrutiny. It looks into the ways in which the rhetorical strategies employed by leaders affect the emotional and normative commitment levels of the employees, which, in turn, dictates the kinds of performance outcomes that the employees deliver. The results show that rhetorical leadership is a powerful tool for enhancing job performance that works primarily through raising the level of commitment that employees feel toward their work. This study adds to the extensive knowledge about leadership dynamics by making clear the crucial roles of communication and commitment that are necessary for reaching the kind of organizational success that results in effective performance outcomes. It is one thing to be an organizational leader; it is another to lead with sufficient communication and commitment such that one’s organization is not just functional but also effective—achieving performance outcomes that matter.